alpha-Actinin and membrane glycoprotein IIIa are different proteins in human blood platelets. - Langer, B G (1982)
It has been suggested that a platelet protein that is very similar to muscle alpha-actinin is identical to the membrane glycoprotein IIIa (GPIIIa) of platelets and is responsible for anchoring actin filaments directly into the plasma membrane of platelets. To determine if alpha-actinin and GPIIIa are related in platelets, we analyzed the purified proteins on 5% sodium dodecyl sulfate/polyacrylamide gels. The two proteins differ in mobility in both the unreduced and reduced states, and they stain differently with silver stain. In addition, alpha-actinin is a prominent component of the detergent-insoluble cytoskeletons of platelets, whereas GPIIIa is absent from these structures. By using monospecific antisera to the individual proteins, it was demonstrated that alpha-actinin and GPIIIa are immunologically distinct. We conclude that alpha-actinin and GPIIIa are different proteins in human blood platelets and that it is unlikely that alpha-actinin is an integral membrane protein.